Modified Atmosphere Packaging Maintains the Sensory and Nutritional Qualities of Post-harvest Baby Mustard During Low-Temperature Storage - Lin, Peixing; Di, Hongmei; Wang, Guiyuan; Li, Zhiqing; Li, Huanxiu; Zhang, Fen; Sun, Bo (Frontiers in Nutrition, 2021)
Baby mustard is a popular, yet highly perishable, Brassica vegetable. There is a need to develop effective methods for maintaining post-harvest qualities of baby mustard. Here, the lateral buds of baby mustard were packed in transparent polyethylene bags with no holes (M0), 6 mm in diameter holes (M1), or 12 mm in diameter holes (M2) and stored at 4°C. The effect of different modified atmosphere packaging (MAP) treatments on the sensory quality, health-promoting compounds, and antioxidant capacity was investigated by comparison with non-wrapped baby mustard. M1 and M2 delayed sensory quality deterioration and slowed declines in the content of ascorbic acid, total phenolics, and glucosinolates and antioxidant capacity during storage. M1 was most effective in prolonging the shelf life (three additional days compared with control lateral buds) and maintaining the content of glucosinolates. However, M0 accelerated the decline in the odor score, acceptability score, and ascorbic acid content and shortened the shelf life of baby mustard by more than 5 d compared with the control. These findings indicate that the effect of MAP treatment depends on the size of the holes in the bag. Based on these results, M1 was an alternative method for prolonging the shelf life and maintaining post-harvest qualities of baby mustard stored at 4°C.